2008
DOI: 10.1089/end.2007.0034
|View full text |Cite
|
Sign up to set email alerts
|

Does the Metabolic Syndrome or Its Components Affect the Outcome of Percutaneous Nephrolithotomy?

Abstract: Our results indicate that the metabolic syndrome and its components (DM and HT) significantly augment auxiliary treatment and complication rates after PCNL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
1
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 24 publications
3
21
1
5
Order By: Relevance
“…Tefekli et al [ 5 ] reported a 9.5% incidence rate for patients with metabolic syndrome undergoing PCNL; they also reported an overall success rate of 96.3% for PCNL and a complication rate of 11.4%. They detected that the risk of major complications was 2.5-times higher in patients with hypertension, 2.7-times higher in patients with DM, and 2.45-times higher in patients with metabolic syndrome [ 5 ] . In their study, the need for auxiliary treatments after PCNL was more common in patients with DM and the metabolic syndrome, but not in those with a BMI of > 30 kg/m 2 and serum lipid abnormalities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tefekli et al [ 5 ] reported a 9.5% incidence rate for patients with metabolic syndrome undergoing PCNL; they also reported an overall success rate of 96.3% for PCNL and a complication rate of 11.4%. They detected that the risk of major complications was 2.5-times higher in patients with hypertension, 2.7-times higher in patients with DM, and 2.45-times higher in patients with metabolic syndrome [ 5 ] . In their study, the need for auxiliary treatments after PCNL was more common in patients with DM and the metabolic syndrome, but not in those with a BMI of > 30 kg/m 2 and serum lipid abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…They detected that the risk of major complications was 2.5-times higher in patients with hypertension, 2.7-times higher in patients with DM, and 2.45-times higher in patients with metabolic syndrome [ 5 ] . In their study, the need for auxiliary treatments after PCNL was more common in patients with DM and the metabolic syndrome, but not in those with a BMI of > 30 kg/m 2 and serum lipid abnormalities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypertension and diabetes mellitus are two patient-related independent predictive factors affecting bleeding risk [6,28,29]. The authors exploring the factors affecting blood loss during PNL concluded that complex renal stones requiring multiple renal tracts are associated with high transfusion rates [6,26,28,30].…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] In a series of 183 diabetic patients who underwent percutaneous nephrolithotomy, Duvdevani and colleagues 16 found that uric acid was the most common stone composition and that these patients had a longer hospital stay than non-diabetics. Surgical time, complications and stone-free rates were not significantly different from those observed in the non-diabetic group.…”
Section: Discussionmentioning
confidence: 99%